Preparation Characterization and Application of Novel TiO2 Membrane in Photocatalytic Reactor - Miao Yingchun (Science Faculty of Chiang Mai University, 2019)
The films with photocatalytic properties were synthesized by solvothermal method, then characterized by XRD, SEM, EDX, FTIR, DRS and electron probe microscopy scanning sequence The anatase TiO2 thin film was found to be compound of 0.27 nm particles,.-with the smooth surface and the thin film thickness of 900 nm. Moreover , the anatase TiO2 thin film was applied to a novel photocatalytic reactor model. Underling the same ultraviolet light and the same optical path, the degradation of the TiO2 films to 120 mL 5 mg/L methyl violet solution was 27.42% (2.5h), and then the dissolution rate of fulvic acid in 30 g lignite sample was 18.6% (1h). The results were superior to the degradation rate and dissolution rate of traditional rotary reactors (16.1% and 8.3%, respectively).